THE OPERATIVE PROFIT MARGIN AND INTEREST COST IN RETAIL FOOD - Vojteski Kljenak, Dragana; Lukic, Radojko; Gavric, Gordana; Gavrilovic, Milan (Economics of Agriculture, 2019)
Both theoretical and practical importance have recently been attached to an analysis of the operating profit margin or earnings before interest, taxes, depreciation and amortization (EBITDA margin) as a measure of the long-term performance of companies. In the integrated financial reporting it is presented through various indicators based on it. In view of this, we have made a comparative analysis of the operating profit margin and its impact on the performance of food trade companies in Serbia and comparable countries. Under the influence of different factors, the dynamics of the size of the operating profit margin of food trading companies in Serbia varies from comparable global food retailers in various countries. Based on the obtained results of empirical research, we can also conclude that the EBITDA margin of the leading food trading companies in Serbia is lower than the in analyzed comparable food retail trade companies from the developed market economies. It points to the conclusion that it is necessary to efficiently manage revenues, costs, profit, assets, and financial structure in order to improve the performance of food trading companies in Serbia in the future. The general conclusion is that it shows a growth tendency and is, nevertheless, lower in comparison to food trading companies from countries of a developed market economy. In order to increase the operating profit margin, as a measure of long-term performance, it is necessary to manage the financial structure of the food trading companies in Serbia as effectively as possible.